2016
DOI: 10.1080/1120009x.2016.1140858
|View full text |Cite
|
Sign up to set email alerts
|

Targeted benefits of prolonged-infusion piperacillin-tazobactam in an in vitro infection model of Pseudomonas aeruginosa

Abstract: Given the inconsistent clinical findings, our goal was to characterize the pharmacodynamics (PDs) of prolonged-infusion piperacillin-tazobactam (TZP) in an in vitro pharmacodynamic model of Pseudomonas aeruginosa. Specifically, the study was designed to investigate the influence of MIC on the activity of prolonged-infusion TZP using pharmacokinetics (PKs) consistent with a non-critically ill patient population. There was no benefit with prolonged- compared with standard-infusion TZP against isolates with susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Zelenitsky et al 39 characterized the pharmacodynamics of prolonged-infusion piperacillin/tazobactam in an in vitro pharmacodynamic model of P aeruginosa . The benefits of prolonged infusion were selective and most likely observed in patients with less susceptible pathogens, ie, prolonged infusion had no advantages over standard infusion against isolates with susceptible MICs of 8 or 16 mg/L, whereas it produced more than twice the final bacterial kill against less susceptible isolates with an intermediate MIC of 32 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Zelenitsky et al 39 characterized the pharmacodynamics of prolonged-infusion piperacillin/tazobactam in an in vitro pharmacodynamic model of P aeruginosa . The benefits of prolonged infusion were selective and most likely observed in patients with less susceptible pathogens, ie, prolonged infusion had no advantages over standard infusion against isolates with susceptible MICs of 8 or 16 mg/L, whereas it produced more than twice the final bacterial kill against less susceptible isolates with an intermediate MIC of 32 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced drug efficacy of piperacillin-tazobactam in combination with amikacin and vancomycin (78% susceptibility) showed better results against various empirical infections 115 and critically ill patients. 116 A pharmacodynamic and prolonged infusion study 117 showed the efficiency of piperacillin-tazobactam against AmpC βlactamase, showing effectiveness against multiple drug-resistant isolates. 118 Inability to cross the biofilm barrier is the most general phenomenon that inhibits the activity of microbes, and clinical isolates of Pseudomonas grown at different time interval have shown the inefficiency of antibiotics.…”
Section: Ureidopenicillin (β-Lactam/lactamase Inhibitor)mentioning
confidence: 99%
“…A one-compartment model, described previously, was used to simulate infection in an immunocompromised host. [9][10][11] The central compartment, containing 250 mL of Mueller-Hinton broth with 25 mg/L calcium and 12.5 mg/L magnesium (Mueller-Hinton II broth, Becton Dickinson & Company, Sparks, MD, USA), was continuously stirred and maintained at 37 C. A computerized pump (Masterflex, Cole-Parmer, Chicago, IL, USA) delivered fresh broth from a reservoir flask through the central compartment to produce the desired elimination t1 =2 . Five clinical MSSA isolates were tested in the IPDM studies.…”
Section: In Vitro Pd Model (Ipdm)mentioning
confidence: 99%
“…The antibiotic concentrations (within 15% of target) in the central compartment were confirmed with antibiotic bioassays using Bacillus subtilis ATCC 6633. 9,16 The PK parameters were verified using linear regression analysis. Experiments were conducted in triplicate on separate occasions.…”
Section: In Vitro Pd Model (Ipdm)mentioning
confidence: 99%